The Influence of Task-Irrelevant Flankers Depends on the Composition of Emotion Categories - Schulte Holthausen, Barbara; Regenbogen, Christina; Turetsky, Bruce I.; Schneider, Frank; Habel, Ute (Frontiers in Psychology, 2016)
Face recognition usually takes place in a social context, where faces are surrounded by other stimuli. These can act as distracting flankers which impair recognition. Previous work has suggested that flankers expressing negative emotions distract more than positive ones. However, the various negative emotions differ in their relative impact and it is unclear whether all negative emotions are equally distracting. We investigated the impact of three negative (angry, fearful, sad) and one positive (happy) facial flanker conditions on target recognition in an emotion discrimination task. We examined the effect of the receiver’s gender, and the impact of two different temporal delays between flanker and target onset, as stimulus onset asynchrony is assumed to affect distractor strength. Participants identified and rated the emotional intensity of target faces surrounded by either face (emotional and neutral) or non-face flankers. Target faces were presented either simultaneously with the flankers, or delayed by 300 ms. Contrary to our hypothesis, negative flankers did not exert stronger distraction effects than positive or neutral flankers. However, happy flankers reduced recognition performance. Results of a follow-up experiment with a balanced number of emotion categories (one positive, one negative and one neutral flanker condition) suggest that the distraction effect of emotional flankers depend on the composition of the emotion categories. Additionally, congruency effects were found to be valence-specific and overruled by threat stimuli. Females responded more quickly and rated targets in happy flankers as less intense. This indicates a gender difference in emotion processing, with greater sensitivity to facial flankers in women. Targets were rated as more intense when they were presented without a temporal delay, possibly due to a stronger flanker contrast. These three experiments show that an exceptional processing of threat-related flanker stimuli depends on emotion category composition which should be considered a mediating factor when examining emotional context effects.